DEVELOPMENT OF INTERACTIVE VIDEO MEDIA BASED ON CTL (CONTEXTUAL TEACHING AND LEARNING) ON FLAT BUILDING MATERIAL GRADE IV MADRASAH IBTIDAIYAH - Najib, Muhammad; Lestari, Nafa Indah Budi; Salfadilah, Fatonah; Supriadi, Muhamad; Janah, Futihatul (AULADUNA: Jurnal Pendidikan Dasar Islam, 2023)
The development of CTL-based interactive video media is motivated by the lack of utilization of media such as videos in the learning process, thus causing a lack of student interest in learning, especially in mathematics subjects. With the use of this media, the learning process becomes more interesting and fun. The purpose of this research is to produce a product in the form of CTL-based interactive video media that is suitable for mathematics subjects on flat building materials. The type of research used is R&D with the 4D model (Define, Design, Development, Dessemination) or called the 4Ps, namely Defining, Planning, Development and Dissemination. This media was validated by media experts and material experts who were then tested on grade 4 Madrasah Ibtidaiyah students totaling 21. The results of the media expert validation obtained an overall average score of 87% with the criteria "Very Good". The results of the material expert validation obtained an overall average score of 78% with "Good" criteria. And the results of class teacher validation in the media field obtained an average score of 79% with the criteria "Good" and in the field of material obtained an average score of 82% with the criteria "Good". While the results of student responses obtained an overall average score of 90% with the criteria "Very Good". So it can be concluded that this CTL-based interactive video is very feasible to use and can increase student learning interest.